A pilot study of function‐based radiation therapy planning for lung cancer using hyperpolarized xenon‐129 ventilation MRI. Issue 3 (19th January 2022) - Ding, Yi; Yang, Lu; Zhou, Qian; Bi, Jianping; Li, Ying; Pi, Guoliang; Wei, Wei; Hu, Desheng; Rao, Qiuchen; Li, Haidong; Zhao, Li; Liu, An; et al.
Abstract: Purpose: Radiation‐induced lung injury (RILI) is a common side effect in patients with non‐small cell lung cancer (NSCLC) treated with radiotherapy. Minimizing irradiation into highly functional areas of the lung may reduce the occurrence of RILI. The aim of this study is to evaluate the feasibility and utility of hyperpolarized xenon‐129 magnetic resonance imaging (MRI), an imaging tool for evaluation of the pulmonary function, to guide radiotherapy planning. Methods: Ten locally advanced NSCLC patients were recruited. Each patient underwent a simulation computed tomography (CT) scan and hyperpolarized xenon‐129 MRI, then received 64 Gyin 32 fractions for radiotherapy. Clinical contours were drawn on CT. Lung regions with good ventilation were contoured based on the MRI. Two intensity‐modulated radiation therapy plans were made for each patient: an anatomic plan (Plan‐A) based on CT alone and a function‐based plan (Plan‐F) based on CT and MRI results. Compared to Plan‐A, Plan‐F was generated with two additional steps: (1) beam angles were carefully chosen to minimize direct radiation entering well‐ventilated areas, and (2) additional optimization criteria were applied to well‐ventilated areas to minimize dose exposure. V20Gy, V10Gy, V5Gy, and the mean dose in the lung were compared between the two plans. Results: Plan‐A and Plan‐F were both clinically acceptable and met similar target coverage and organ‐at‐risk constraints ( p > 0.05) except for the ventilated lungs. Compared with Plan‐A, V5Gy (Plan‐A: 30.7 ± 11.0%, Plan‐F: 27.2 ± 9.3%), V10Gy (Plan‐A: 22.0 ± 8.6%, Plan‐F: 19.3 ± 7.0%), and V20Gy (Plan‐A: 12.5 ± 5.6%, Plan‐F: 11.0 ± 4.1%) for well‐ventilated lung areas were significantly reduced in Plan‐F ( p < 0.05). Conclusion: In this pilot study, function‐based radiotherapy planning using hyperpolarized xenon‐129 MRI is demonstrated to be feasible in 10 patients with NSCLC with the potential to reduce radiation exposure in well‐ventilated areas of the lung defined by hyperpolarized xenon‐129 MRI.